Practical Theology Amid Environmental Crises - McCarroll, Pamela R.; Kim-Cragg, HyeRan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The field of Practical Theology has been slow to address the realities of environmental crises in its teaching, research, and practice. While there are relevant chapters and articles in books and journals, they are often difficult to find and their contents reveal a lack of conversational engagement. The present volume seeks to change this reality by bringing together key voices in the field from across the world to engage with the theme of Practical Theology amid Environmental Crises. It is the first of its kind. With this volume, we seek to initiate a sustained conversation on the topic by considering the implications of the crises for research, teaching, and practice in the field. With passion and a sense of grounded hope, we invite you to join us in this difficult but important conversation.